Discrimination with reason? The policy of reservations in the United States, India, and Malaysia - Nesiah, Devanesan (Delhi ; New York : Oxford University Press, 1997)
Reservation policies have been the subject of heated debate wherever they have operated. Various schemes for reverse discrimination based on gender, ethnicity, or geographical location have been in force in a number of developed and developing countries, and have evolved in response to certain socio-political problems arising from persistent disparities and a history of discrimination and marginalization. Affirmative Action in the USA, Protective Discrimination in India, Bumiputra Preferences in Malaysia involve reverse discrimination designed to compensate for existing inequalities. The author asks whether such policies are in fact sound and accomplish the ends they are designed to fulfill. Discrimination with Reason is an inter-country study of affirmative action. It is multidisciplinary both in its analytical approach and substantive focus, bringing together the fields of public policy, law, education, sociology and history. The book evaluates the theoretical aspects as well as the practical implementation of the policy
Keywords: Discrimination -- United States; Discrimination -- India; Discrimination -- Malaysia; United States -- Race relations; United States -- Ethnic relations; India -- Race relations; India -- Ethnic relations; Malaysia -- Race relations; Malaysia -- Ethnic relations